Exploring the engagement process between humans and intelligent virtual assistants - Garrotes, Patrícia Saturnino Mateiro Silva (2021)
Happy and loyal customers are two of the main objectives for all brands, and it represents a constant challenge which involves and depends a lot on the brand-consumer relationship. Both customer happiness and loyalty are consequences of a good relationship between the two parties, which is formed through engagement. This study aims to better understand the engagement process between Humans and Intelligent Virtual Assistants, and the influence of intimacy and attachment in this process of interaction, identification and relationship. For this purpose, a conceptual framework was created and tested, based in part on the attachment theory, in order to better understand the engagement process between Humans and IVAs. The study conducted used primary data, obtained through a questionnaire, and was employed to better understand the model and to test the hypotheses developed. The results demonstrate all hypotheses are supported by the model, and people do, in fact, create an emotional relationship with their IVAs on a daily basis context, the attachment strength influences customer engagement levels. Furthermore, they also show that there is a clear relationship of positive influence between customer engagement and customer loyalty and happiness.